Oiseleurs en temps d’extinction - Charles Stépanoff; Tiffany Chérix Dorsaz; Léa Filiu; Gabriel Tropini (Revue d'ethnoécologie)
Recent studies highlight the correlation between the decline of local food networks, loss of ecological diversity, and species extinctions. Building upon this new holistic biocultural perspective, this article examines the case of French bird trapping practices legally defined as ’traditional hunting.’ While these trapping techniques have been subject to controversy for many years, there has been no comprehensive ethnoecological study on them to date. Based on a series of field surveys, this article documents the techniques and ecological knowledge involved in various ’traditional hunting’ practices in France: ’tendelles’ in the Causses, ’tenderies’ for thrushes and ’tenderies’ for lapwings in the Ardennes, ’pantes,’ ’pantières,’ and ’matoles’ in Aquitaine, and ’gluaux’ in Provence. The study hignlights the largely unrecongnized functional impact of these practices in socio-ecosystems and their role in the intergenerational transmission of local community ties to their environment through networks of sociability and exchange. It documents communication with birds, the relationship with decoy birds, forest shelters constructed for hunting, as well as the sharing of captures and their role in local commensality. Finally, it outlines an analysis of the cosmological foundations of long-standing conflicts related with bird trapping.